Financial overload experienced by family caregivers of chemical dependents - Keity Laís Siepmann Soccol; Marlene Gomes Terra; Danilo Bertasso Ribeiro; Sadja Cristina Tassinari de Souza Mostardeiro; Joze Karlem da Silva Teixeira; Valquíria Toledo Souto; Eliane Tavares da Silva (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211264 Aim: to describe the circumstances that cause financial burden experienced by family caregivers of addicted individuals. Method: descriptive and exploratory qualitative research. The study included 11 family caregivers of addicted individuals attending a Psychosocial Care Center for alcohol and other drugs. The data were collected through individual interviews, which were open and recorded. For data analysis, the thematic Content Analysis was adopted. Results: addiction causes damage and financial difficulties for the family. Still, it jeopardizes family relationships and generates physical and psychological overloading for the caregiver. Conclusion: living together with a chemically dependent individual influences in the economic situation of the family and, thus, reflects in family and social relationships, causing different damages to the family.